The importance of sullage (grey-water) treatment for the restoration and conservation of urban streams - Idris, Azni; Wan Azmin, Wan Nor; Mohd Soom, Mohd Amin; Mamun, Abdullah Al (Taylor & Francis, 2005)
Sullage (grey-water) is one of the major point pollution sources, which is discharged from residential and commercial areas into the rivers without any treatment. This study was conducted to determine the pollution characteristics of sullage from a 6.14-hectare residential area where it is discharged into an urban stream without any treatment; and thereafter, to evaluate its probable consequences on the water quality of urban streams. Analyses of the hourly samples revealed that the sullage from residential area was polluted due to high concentration of BOD, COD, Ammoniacal Nitrogen (AN), Orthophosphate (PO4) and TKN, and low concentration of DO. Mean concentrations of the above-mentioned parameters from 72 samples were 51, 123, 5.4, 2.15, 2.15 and 1.62 mg/l, respectively. Further analyses of data revealed that, on average, the sullage was equivalent to Class V water as defined by the water quality index (WQI) in NationalWater Quality Standards (INWQS) of Malaysia. Most of the urban streams drain return water (wastewater) from the settlements and lack adequate baseflow to dilute the wastewaters. As such, if the return waters are not treated then the urban streams shall never be able to achieve the required goals. Domestic sewage and industrial wastewaters are treated to some extent, to achieve the standards stated in Environmental Quality Act, 1979. On the contrary, although quantity and quality of sullage plays important role on stream water quality, it is neither taken care of by any agency nor controlled by any standard. As such, it is important to make necessary technical, institutional and legal arrangement to treat sullage up to certain standard before it find its way into the urban streams.